PENERAPAN PEMBELAJARAN ELEARNING UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA TERHADAP MATA KULIAH PERENCANAAN PEMBELAJARAN DI PGSD FKIP UNSYIAH - Mislinawati Mislinawati. (Jurnal Pesona Dasar, 2019)
In accordance with the demands of technological and information development lecturers are required to make innovation in learning. One of the innovation that lecturers can apply in their teaching is learning through the use of e-learning. The approach in this study used qualitative research with the research subjects of the Unsyiah FKIP PGSD students who attended the learning planning course. The technique of data collection is done through observation and interviews. The results of the study show that students can understand the material well through e-learning. With various forms of material used such as modules, PPT and video can help students understand the material of each topic. The conclusions in this study through the use of e-learning can improve students' understanding of learning planning courses. This can be seen from the scores of the assignments and the quiz that is done on each topic gets good grades.